Inclusion effect of jack mackerel meal in olive flounder (Paralichthys olivaceus) diet substituting blended fish meal with tuna by-product meal on growth, feed availability, and economic efficiency - Islam, Md. Rabiul; Cho, Sung Hwoan; Kim, Taeho (Frontiers in Marine Science, 2024)
The low fish meal (FM) diet commonly causes deteriorated palatability, and eventually leads to lowered feed consumption and growth performance of fish. This study was, therefore, designed to determine inclusion impact of the graded levels of jack mackerel meal (JMM) in olive flounder (P. olivaceus) diets replacing 50% FM with tuna by-product meal (TBM) on growth, feed availability, biochemical composition, blood chemistry, and economic efficiency. Six isonitrogenous (55.5%) and isolipidic (10.0%) diets were formulated. Sixty percent FM was incorporated in the control (Con) diet. In the Con diet, fifty percent of FM was replaced by TBM, and then 10, 20, 30, 40, and 50% JMM were included at the cost of FM, referred as the TJ10, TJ20, TJ30, TJ40, and TJ50 diets, respectively. Three hundred and sixty juvenile fish (18.0 ± 0.01g; mean ± SD) were delivered into 18, 50-L flow-through tanks. All diets were randomly assigned to triplicate groups of fish. Fish were hand-fed to apparent satiation twice daily for 56 days. Weight gain, specific growth rate, and feed consumption of fish fed the TJ30, TJ40, and TJ50 diets were significantly (P < 0.001, P < 0.001, and P < 0.002, respectively) greater than those of fish fed the Con and TJ10 diets, but not significantly (P > 0.05) different from those of fish fed the TJ20 diet. Feed utilization, proximate composition, amino acid profiles, and blood chemistry of fish were not significantly (P > 0.05) altered by dietary treatments. However, the TJ30 diet was the most recommendable to farmers in terms of economic profit index (EPI). Conclusively, 30% inclusion of JMM is the most recommendable in the olive flounder diet substituting 50% FM with TBM based on growth performance, feed availability, and EPI.